Le refus du monde tel qu’il est : vertus et ambivalences de quelques fictions contemporaines (Peyrebonne, Haenel, Vasset) - Pascal Mougin (ReS Futurae)
Three French novels published recently consider the contemporary reality, in its social, economic and political aspects, in a counterfactual way: Philippe Vasset, La Conjuration (Fayard, 2013), Yannick Haenel, Les Renards pâles (Gallimard, 2013), Nathalie Peyrebonne, Rêve général (Phébus, 2013). These three fictions of secession and dissident tilting, ie the collective refusal of the world as it is, radicalize, extrapolate or transfigure other current forms of protest. What this corpus reworks the concept of strangeness, fantasy and utopia? How do these alternative dramas imply on the behalf of the reader, perhaps less the traditional temporary suspension of disbelief than a "want to believe" that is convergent with the evolution of critical thinking itself, when theories of emancipation, wich have no more certainty regarding the revolutionary inevitability, bet more on the necessity of belief in alternative thought? Can these fictions, finally, contribute back to the critical business and dissident practices? Should we believe, with Yves Citton, "in the unpredictable power of the infinitesimal" or on the contrary, with Fredric Jameson, that "the artistic production brandished as utopian model of an alternative social life is itself a closed book" within a globalized economic and cultural system? One must point the ambivalence of these fictions, upbeat and engaging on one side, proxy and desperate or opportunistic and complacent on the other.